Pengaruh Arus Kas Operasi, Arus Kas Investasi, Arus Kas Pendanaan dan Laba Akuntansi terhadap Return Saham - Mafsud, Muhamad; Meirini, Dianita (Jurnal Informatika Ekonomi Bisnis, 2023)
The capital market is a place where investors invest their capital in the hope of a return in the form of a return on investment. Investors use financial reports in investing but cannot analyze the stock returns that will be received starting operating cash flow, investment cash flow, and funding cash flow. The method used is a quantitative method with multiple linear regression tests using the eviews data processing application. The results of this study. The coefficient X1 (cooperative cash flow) is 0.170479413211 which means that if the cooperative's cash flow increases, it will cause an increase in stock returns with no positive effect with a significant value of 0.7170 > 0.05. The coefficient X2 (Investment Cash Flow) on stock returns (the dependent variable Y) has no effect with a significant value of 0.3113 > 0.05. The X3 coefficient (Funding Cash Flow) on stock returns (Y dependent variable) has no effect 0.6658 > 0.05 and the X4 coefficient (Accounting Profit) is 0.352300 which means that if accounting profit increases once it will cause an increase in Stock Return (dependent variable Y) or has a positive effect of 0.964377644814 when other variables are constant with a significant value of 0.000 <0.05.